Pilot evaluation of a recovery group for psychosis inpatient wards: patients' views and recommendations. (1st April 2018) - Christoforou, Rania; Clarke, Amory; Bell, Victoria
Objectives: Recovery-orientated care emphasises hope, self-belief and social connectedness. However, there are a limited number of studies of recoveryoriented practice in mental health inpatient settings for psychosis. The aim of this study was to investigate the acceptability of a newly devised psychologicallyinformed ward-based recovery group for individuals with treatment refractory psychosis. Method: This was a qualitative study. Two groups were run within two psychosis inpatient wards. Patients' views were investigated using a semi-structured interview. Results: Five themes were deducted using thematic analysis, which included understanding of the group content, learning about recovery and coping with mental health problems, different levels of wellness, usefulness of media usage in the group and willingness to participate in the group again. Conclusions: The group was well received by patients and it may hold promise as one way to increase the availability of recovery-oriented discussions for inpatients with psychosis. Future studies could address methodological problems and adapt the content of the group based on feedback from patients.